Advances in diagnosis, clinical management and molecular characterization of ovarian Brenner tumors - Valentina Zanfagnin; Tiffany Lee; Chengquan Zhao; Tiannan Wang (BMJ Publishing Group, 2023)
Brenner tumors is a very uncommon ovarian epithelial neoplasm, morphologically resembling the transitional cell neoplasm of urinary tract. It is further classified into three subtypes as a disease spectrum based on histological examination and tumorigenesis: benign Brenner tumors, borderline Brenner tumors (BBTs), and malignant Brenner tumors (MBTs). The etiology of these tumors is not well understood, and literature is limited due to the rarity of this entity, but recent advances, particularly in molecular alterations, have emerged. The scope of this review is to provide an update on the clinical, histopathological, and most recently, molecular characterizations of ovarian Brenner tumors.